Bioenergy: Socio-Economic and Environmental Implications and Future of Biofuels - Ahlam Skaib; Rema Zedan (African Journal of Advanced Pure and Applied Sciences, 2023)
Bioenergy is a promising energy source, by 2040, the estimated increase in global energy demand over present levels is about 28%. In terms of generating fuels, either solid or liquid. To mitigate human climate change, biofuels can replace fossil fuels. Emissions of greenhouse gases. Yet, evidence that biofuels are generated in a sustainable manner should be the foundation for any policy decisions about them. To this goal, life cycle assessment (LCA) offers details on the environmental effects linked to the manufacturing of biofuels. Here, we examine developments in biomass conversion to biofuels and their effects on the environment. through life cycle analysis. Gasification, combustion, pyrolysis, enzymatic hydrolysis pathways, and fermentation are examples of processes. Gasification, combustion, and pyrolysis are examples of low temperature thermochemical processes, which occur below 300 °C, and high temperature processes, which occur above 300 °C. In contrast to gasification, which operates at temperatures between 800 and 1300 °C, pyrolysis operates at a relatively lower temperature of up to 500 °C. We concentrate on the following topics: 1) the benefits and drawbacks of the thermochemical and biochemical conversion routes of biomass into various fuels, as well as the possibility of integrating these routes for better process efficiency; 2) methodological approaches and key findings from studies on biomass to biofuel conversion pathways published from ; and 3) social, economic, and environmental trends and knowledge gaps in biomass conversion into biofuels using thermochemical and biochemical methods. The circular economy is hopeful about the convergence of hydrothermal and biochemical routes of bioenergy